The Effect of Motored Houses on Coliform Pollution in Marine Waters and Its Impact On Public Health, Jayapura City - Simbiak, Herlin Mienatha; Imoliana, Wilhelmina Tania; Krismono, Krismono; Rahardjo, Djoko (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2023)
An anchored house, which stands above seawater, is common in North Jayapura and South Jayapura. Wooden foundations support these houses. People frequently contract waterborne diseases when they use or consume water that is contaminated with pathogenic bacteria, such as coliform bacteria from human feces. In these areas, high levels of coliform bacteria can have an impact on water quality and public health. This study looks into how anchored houses affect total coliform contamination, the number of cases of waterborne disease (WBD), and the link between demographic factors, water quality, and WBD cases. We use the Most Probable Number (MPN) method to detect total coliform bacteria in marine waters. It consists of an initial test using LBS and LBD media for prediction, followed by a second test using Brilliant Green Lactose Bile Broth (BGLBB) media for confirmation. We also use observation and interview methods to identify WBD cases in anchored housing in North Jayapura and South Jayapura districts. North Jayapura has the highest coliform bacteria contamination in marine waters, with an average of 25.7 MPN/100 mL. Similarly, the highest contamination in clean water is in North Jayapura, averaging around 347.6 MPN/100 mL. The demographic characteristics in both districts are mostly men aged 18–65 years with high school education and occupations such as housewives and fishermen. The South Jayapura sub-district has the highest incidence of WBD. Anchored houses have no significant effect on water quality or the incidence of WBD, and there is no correlation between water quality and WBD incidence.